Biosorption of Total Chrome Metals on Leather Tannery Liquid Waste Using Tofu Dregs - Pangestu, Muhammad Aji; Pracesa, Yahya Ardian Yuma; Perwitasari, Dyah Suci (Future Science)
Chrome metal was the main element in tannery liquid waste. Chrome was included in B3 waste and has the potential to destructed or contaminated surroundings. The use of natural material as an adsorbent medium for b3 heavy metal currently was being studied. Tofu dregs were an alternative that can be used as biosorbent. This study's aim was to adsorbed total chrome metal in tannery liquid waste. The operating conditions took place at a pH of 7 and a stirring speed of 200 rpm. The analysis using Atomic Absorption Spectrometer (AAS) showed that the total chromium adsorption efficiency occurs in the addition of 6 grams of biosorbent with a contact time of 160 minutes. The adsorption percentage was 98% and the residual level total chromium metal in the tannery liquid waste was 0,33 mg/L after adsorption. These results have fulfilled the quality standard of the leather tannery wastewater that was allowed to be released into the environment with maximum total chrome metal levels of 0,5 mg/L. The total chromium metal biosorption in this study followed the Langmuir isotherm and took place as chemisorption.